2002
DOI: 10.2320/matertrans.43.1719
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Hot-pressed Boron Suboxide (B<SUB>6</SUB>O)

Abstract: Boron suboxide (B 6 O) sintered bodies were prepared by a solid state reaction and a hot pressing method. The thermoelectric properties of B 6 O were compared with those of B 4 C. The electrical conductivity was smaller than that of B 4 C, and the Seebeck coefficient was twice as large as that of B 4 C indicating p-type conduction. The hopping conduction of electronic charge carriers was suggested from the temperature dependencies of the electrical conductivity and mobility. The thermal conductivity was greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…In terms of impurities, our results suggest that typical doping schemes do not apply to B 6 O due to the unique bonding environment exhibited by the underlying icosahedral structure [13,14], with the majority of substitutional and interstitial impurities acting as deep donors or acceptors. However, we do identify a complex consisting of H and C substituting on the oxygen site that acts as a shallow acceptor and is likely responsible for the observed p-type conductivity in this oxide semiconductor [12]. Our results confirm B 6 O to be a plausible candidate for a p-type TCO and additionally show implications for ambipolar doping if the stoichiometry and background impurity concentration can be controlled.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…In terms of impurities, our results suggest that typical doping schemes do not apply to B 6 O due to the unique bonding environment exhibited by the underlying icosahedral structure [13,14], with the majority of substitutional and interstitial impurities acting as deep donors or acceptors. However, we do identify a complex consisting of H and C substituting on the oxygen site that acts as a shallow acceptor and is likely responsible for the observed p-type conductivity in this oxide semiconductor [12]. Our results confirm B 6 O to be a plausible candidate for a p-type TCO and additionally show implications for ambipolar doping if the stoichiometry and background impurity concentration can be controlled.…”
Section: Introductionmentioning
confidence: 50%
“…The screening found that this compound exhibits a low hole effective mass (around 0.6 compared to >2 for current Cu-based p-type TCOs such CuAlO 2 [7], CuCrO 2 [8], or SrCu 2 O 2 [9]) and a large band gap (3 eV according to G 0 W 0 computations). Boron suboxide has mainly been studied as a hard coating material [10,11] and we are aware of only one paper that measured its transport properties [12]. While Akashi et al concluded that B 6 O can be p-type as-grown, their samples were largely porous and may not accurately reflect the fundamental bulk properties [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas none of our candidates have ever been tested (or even suggested) as TCOs, doping studies indicating p -type dopability have already been reported experimentally or computationally for several of them. B 6 O has been experimentally measured to show p -type conductivity31. It has been demonstrated experimentally that PbZr 0.5 Ti 0.5 O 3 can be grown as p -type32, but some recent computations on PbTiO 3 seem to indicate an oxygen vacancy low in energy even in oxidizing conditions33.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis procedure is described in detail elsewhere 1 . The TEM specimens were prepared by gently crushing and the B 6 O fragments were dispersed on the holey carbon films coated copper grids.…”
Section: Materials Fabrication and Nanoindentationmentioning
confidence: 99%